Sosialisasi Literasi Pengelolaan Keuangan Kepada Remaja di Desa Kelambir Lima Kebun Kecamatan Hamparan Perak - Handriyani Dwilita; Ivanka, Rara (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The purpose of this community service is to improve the understanding of financial management literacy to teenagers in Kelambir Lima Kebun Village, Hamparan Perak District. The specific target in this community service is that the teenagers of Kelambir Lima Kebun Village know how to manage finances. The materials presented in this community service are: what is financial management literacy and how to implement it. The material presented in this community service is: what is financial management literacy and how to implement it, which will affect the financial condition of the teenagers of Kelambir Lima Kebun Village so that the teenagers get solutions in financial management. From this community service, the results show that the teenagers of Kelambir Lima Kebun Village have known and understood the importance of understanding financial management so that they will be able to manage the flow of money in and out and then know its use.